Pharmacological Treatment of Gastritis: A Narrative Review with a Systematic Literature Search - Kim, Bokyung; Huh, Jung; Kim, Sang Gyun; Ahn, Ji Yong; Kim, Ji Won (Gut and liver, 2025)
Gastritis, characterized by gastric mucosal inflammation, is a common gastrointestinal disorder with diverse etiologies, such as infection, nonsteroidal anti-inflammatory drugs use, and autoimmune conditions. Pharmacological treatment aims primarily to heal the mucosa and resolve symptoms, and such treatments include mucoprotective agents, histamine-2 receptor antagonists (H2RAs), proton pump inhibitors (PPIs), and potassium-competitive acid blockers (P-CABs). Mucoprotective agents enhance gastric mucosal protection through multiple mechanisms, such as by promoting mucosal regeneration, reducing inflammation, and mitigating oxidative stress. Clinical trials have highlighted the effectiveness of these agents in promoting endoscopic healing and ameliorating symptoms, underscoring the clinical significance of these agents. H2RAs have been extensively used to manage gastritis due to their proven efficacy in reducing gastric acid secretion and promoting mucosal healing. Additionally, PPIs along with newer P-CABs provide robust acid suppression and have shown the ability to rapidly relieve symptoms, thus increasing the number of available treatment options. Since each pharmacological agent offers distinct therapeutic benefits, treatment should be selected based on an individual patient's needs and clinical context.